Comparative study of pulse oximetry and ankle-brachial index as a screening test for asymptomatic peripheral vascular disease in type 2 diabetes mellitus against color doppler ultrasonography as reference standard - Deep, Hardeep S.; K., Kamaldeep; Mahajan, Devinder S.; Brar, Hargurpal S. (International Journal of Advances in Medicine, 2019)
Background: Currently about 35 million Indians are reported to suffer from diabetes mellitus, a significant proportion of whom are either undiagnosed or diagnosed but undertreated leading to poor glycemic control. This leads to accelerated development of macrovascular complications like Peripheral Vascular Disease (PVD). As most of the patients are asymptomatic, hence, early detection and treatment of PVD in patients with diabetes mellitus carries utmost importance. Methods: The present study was undertaken in SGRDIMSAR, Amritsar on 100 patients of type 2 Diabetes Mellitus with asymptomatic PVD. The diagnostic accuracy of Ankle-Brachial Index (ABI) and pulse oximetry as a screening tool was compared against Color Doppler ultrasonography as the reference standard. Results: The sensitivity, specificity, positive predictive value and negative predicted value of pulse oximetry to diagnose asymptomatic PVD in diabetics was found to be 98.31% (95% CI: 90.91-99.96), 41.46% (95% CI: 26.32- 57.89), 70.73% (95% CI: 65.08-75.81) and 94.44% (95%CI: 70.19-99.19) respectively. The sensitivity, specificity, positive predictive value and negative predicted value of ABI to diagnose asymptomatic PVD in diabetics was found to be 77.97% (95% CI: 65.27-87.71), 97.56% (95% CI: 87.14-99.94), 97.87% (95% CI: 86.85-99.69) and 75.47% (95% CI: 65.51-83.29) respectively. Conclusions: Pulse oximetry is better than ABI for the screening for asymptomatic PVD among diabetics. However, ABI is more accurate as compared to pulse oximetry in diagnosing asymptomatic PVD in diabetics.